Albuminuria and Kidney Function Independently Predict Cardiovascular and Renal Outcomes in Diabetes - Ninomiya, Toshiharu (American Society of Nephrology, 2009)
There are limited data regarding whether albuminuria and reduced estimated GFR (eGFR) are separate and independent risk factors for cardiovascular and renal events among individuals with type 2 diabetes. The Action in Diabetes and Vascular disease: preterAx and diamicroN-MR Controlled Evaluation (ADVANCE) study examined the effects of routine BP lowering on adverse outcomes in type 2 diabetes. We investigated the effects of urinary albumin-to-creatinine ratio (UACR) and eGFR on the risk for cardiovascular and renal events in 10,640 patients with available data. During an average 4.3-yr follow-up, 938 (8.8%) patients experienced a cardiovascular event and 107 (1.0%) experienced a renal event. The multivariable-adjusted hazard ratio for cardiovascular events was 2.48 (95% confidence interval 1.74 to 3.52) for every 10-fold increase in baseline UACR and 2.20 (95% confidence interval 1.09 to 4.43) for every halving of baseline eGFR, after adjustment for regression dilution. There was no evidence of interaction between the effects of higher UACR and lower eGFR. Patients with both UACR >300 mg/g and eGFR <60 ml/min per 1.73 m(2) at baseline had a 3.2-fold higher risk for cardiovascular events and a 22.2-fold higher risk for renal events, compared with patients with neither of these risk factors. In conclusion, high albuminuria and low eGFR are independent risk factors for cardiovascular and renal events among patients with type 2 diabetes.